2016
DOI: 10.1016/j.apsusc.2016.08.127
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morphology and defect density on electron transfer of electrochemically reduced graphene oxide

Abstract: Electrochemically reduced graphene oxide (ERGO) is widely used to construct electrochemical sensors. Understanding the electron transfer behavior of ERGO is essential for its electrode material applications. In this paper, different morphologies of ERGO were prepared via two different methods. Compared to ERGO/GCEs prepared by electrochemical reduction of pre-deposited GO, more exposed edge planes of ERGO are observed on the surface of ERGO-GCE that was constructed by electrophoretic deposition of GO. The defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 47 publications
(54 reference statements)
4
19
0
Order By: Relevance
“…The surface morphology of unmodified and modified GC-ERGO electrodes was further examined using SEM (Figure S5A,B from Supporting Information). The micrographs reveal an incomplete coverage of the GC substrate with agglomerates consisting of stacked ERGO sheets, in line with previous observations [58]. Moreover, there seems to be no apparent difference between the electrode surface morphology before and after modification.…”
Section: Characterization Of Modified Electrodessupporting
confidence: 90%
“…The surface morphology of unmodified and modified GC-ERGO electrodes was further examined using SEM (Figure S5A,B from Supporting Information). The micrographs reveal an incomplete coverage of the GC substrate with agglomerates consisting of stacked ERGO sheets, in line with previous observations [58]. Moreover, there seems to be no apparent difference between the electrode surface morphology before and after modification.…”
Section: Characterization Of Modified Electrodessupporting
confidence: 90%
“…As an alternative to these rough and defective methods, the hydrothermal and electrochemical reduction methods [ 5 , 19 ] appear as green methods because they use moderate temperatures and pressures in aqueous solutions [ 20 ]. The effects that the morphology and defect density have on the electron transfer of electrochemically reduced graphene oxide were published and indicated that both defect densities and edge planes of ERGO play crucial roles in the electron transfer kinetics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, of the large energy demand is one of the major drawbacks for thermal reduction process [32]. Fortunately, a one-step facile route to form rGO from GO suspension on substrate has been identified by electrochemical reduction method, as known as cyclic voltammetry (CV) principle [33].…”
Section: Chemical Exfoliation Methodsmentioning
confidence: 99%